The Role of Community Sports Programs in Promoting Physical Activity Among Adolescents in Belgium - Carlos Martínez (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
This study investigates community sports initiatives' role in encouraging teenagers in Belgium to engage in physical exercise. Programs for community sports give teenagers easily accessible chances to participate in many sports and activities after school. The research was based on primary data analysis to determine whether the research used Smart PLS software and generated informative results, including descriptive statistics, correlation coefficient analysis, and the smart PLS Algorithm model between them. These programs give Adolescents social interaction, skill development, and better health outcomes. Community sports programs are also essential for encouraging diversity and inclusivity in communities and reducing sedentary lifestyles. These programs assist teenagers' overall development and well-being by offering a supportive atmosphere and good role models. They also help adolescents form lifetime healthy living habits. The overall result found a positive and significant relation between community sports programs in promoting physical activity among adolescents in Belgium. In Belgium, funding community sports initiatives is crucial to developing a young population that is both socially and physically engaged.